Violência Policial contra minorias sociais no Brasil e na Espanha: justificativas para o posicionamento de estudantes universitários - Oliveira, Thiago Morais (2013)
The overall aim of this thesis was to investigate whether police violence is more tolerated when the victim is a member of a social minority (e.g. Black in Brazil, and Moroccan immigrants and Romanian gypsies in Spain). This was therefore a thesis on racial prejudice and discrimination in Brazil, and xenophobia and discrimination in Spain. The specific objectives were: a) to analyze the moderating role of a set of psychosocial variables in adopting a position on police violence (e.g. Prejudice, Schwartz's Universal Theory of Basic Human Values, PVQ-24 Psychosocial Values, and Belief in a Just World), and b) to analyze the reasons given by the participants for the positions taken regarding police violence. To achieve these objectives, two studies, with quasi-experimental design, were conducted. In the first, the participants were Spanish university students (n= 207), with ages between 17 and 31 years (M= 20.2,SD= 2.68), and in the second, Brazilian university students (n= 114), with ages between 17 and 56 (M= 23.5,SD= 6.72). The instrument used in both countries began by presenting a scenario of police violence against a member of a social minority who was subsequently found guilty of the offense for which he/she was a suspect. This was followed by a set of open questions, in which the participant was asked to explain his/her position on the situation described. Next, the rest of the variables were presented, all in a six-point Likert format. And finally, the sociodemographic characteristics of the participants were requested. With regard to the moderation analysis results, in the Spanish sample the following variables showed a significant interaction effect with the scenarios presented, i.e. they moderated the scenario's effect on the tolerance for police violence: prejudice; Schwartz's values subsystems; the PVQ-24 psychosocial values subsystems. However, the results for the moderating role of Belief in a Just World were not statistically significant. The Brazilian results also showed significant effects in the interaction of the variables studied with the scenarios presented, with the exception of Schwartz's values subsystems, since the psychometric analyses conducted had shown that the instrument did not meet the criteria that would allow for its use in Brazil. Further, the results regarding Belief in a Just World were only marginally significant. Thus a complementary study was conducted in Brazil, with an instrument similar to the previous one, but in this case the victim of police violence was innocent. In this situation the results were statistically significant, as expected. Regarding the analysis of discursive repertoires, in Spain most participants presented justifications for tolerating police violence against social minorities. In Brazil the results also followed this direction. These results are discussed, with emphasis on their ecological validity, in the sense that it was quite possible to produce a situation from which prejudice and discrimination could emerge. In closing, we hope that the results presented here may support future discussion and intervention directed at an actual change in the way members of social minorities are seen in contemporary societies.